The clinical utility of two human portable blood glucose meters in canine and feline practice. (21st January 2014) - Domori, Asuka; Sunahara, Ayano; Tateno, Morihiro; Miyama, Takako Shimokawa; Setoguchi, Asuka; Endo, Yasuyuki
<x xml:space="preserve">Abstract</x> Background Portable blood glucose meters (PBGMs) are useful for serial measurements of blood glucose and creation of blood glucose curves in veterinary practice. However, it is necessary to validate PBGMs designed for people for veterinary use. Objectives Our objective was to evaluate the accuracy of 2 PBGMs designed for people for use in dogs and cats. Methods The blood glucose levels were determined in blood samples collected from 69 dogs and 26 cats admitted to the Kagoshima University Veterinary Teaching Hospital, using a MEDISAFE [PBGM‐T] and an Antsense III [PBGM‐H], and a FUJI DRI‐CHEM 7000V as reference method. The correlations and agreements among the results were statistically analyzed. Results Simple regression analyses revealed a high correlation between values from both PBGMs and the reference method in both dogs and cats. However, Passing–Bablok regression and Bland–Altman analyses revealed that the data from both PBGMs did not show statistical agreement with the reference values. Concordance correlated coefficients were moderate for the PBGM‐T and almost perfect for the PBGM‐H for canine samples, and were poor for the PBGM‐T and substantial for the PBGM‐H for feline samples. Hematocrit values significantly affected the results of the PBGM‐T, but not the PBGM‐H. Error grid analyses revealed that all measurements from both PBGMs would lead to acceptable treatment decisions. Conclusions Our findings suggest that both PBGMs, especially the PBGM‐H, would be clinically useful in small animal practice, although there was a bias between each PBGM and the reference method.